2006
DOI: 10.1111/j.1600-051x.2006.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between markers of metabolic control and inflammation on severity of periodontal disease in patients with diabetes mellitus

Abstract: The level of glycaemic control as measured by HbA1c emerged as the most consistent risk factor associated with the extent and severity of periodontal disease in this study cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
89
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 33 publications
16
89
2
7
Order By: Relevance
“…28 On the contrary, other researchers have demonstrated that glycemic control worsens with the increase in the severity of periodontal disease. 29,30 For example, Lim et al, 29 results depict a positive association between HbA 1c levels and the percentage of sites with PD >5mm. The reason suggested by the authors for poorer periodontal health among patients with poor glycaemic control was that the hyperglycaemic state results in accumulation of advanced glycated end products.…”
Section: Discussionmentioning
confidence: 97%
“…28 On the contrary, other researchers have demonstrated that glycemic control worsens with the increase in the severity of periodontal disease. 29,30 For example, Lim et al, 29 results depict a positive association between HbA 1c levels and the percentage of sites with PD >5mm. The reason suggested by the authors for poorer periodontal health among patients with poor glycaemic control was that the hyperglycaemic state results in accumulation of advanced glycated end products.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 Persons with poorly controlled DM also present more severe periodontal disease than do those with well-controlled DM. 4,5 Several mechanisms have been proposed to explain the periodontal etiopathogenesis in patients with DM. 3,6 Significant differences may be present in…”
mentioning
confidence: 99%
“…However, it has been reported that periodontitis is one of the first clinical manifestations of diabetes (7) and is recognized as a common complication in diabetic patients (8), particularly in poorly controlled diabetics (9). As an infectious-initiated inflammatory condition, periodontal disease may result in a systemic chronic inflammatory challenge that may have a significant impact on metabolic control in diabetics (10).…”
mentioning
confidence: 99%